What Promotes the Happiness of Vacationers? A Focus on Vacation Experiences for Japanese People During Winter Vacation - Kawakubo, Atsushi; Oguchi, Takashi (Frontiers in Sports and Active Living, 2022)
Several studies on tourism have examined the effects of vacation and travel on individuals’ well-being. However, relatively little is known about the underlying psychological factors and mechanisms. Therefore, this study aimed to investigate the effects of a winter vacation on individuals’ well-being. A total of 507 participants (255 men and 252 women) completed three questionnaires at three different time points. The questionnaires comprised psychological scales and items seeking demographic information so that the changes in their well-being could be assessed. The results revealed that people who traveled had higher subjective well-being than those who did not. Moreover, of the four elements of the recovery experience, mastery was the only one that influenced subsequent subjective well-being. The findings suggest that it is crucial not only to take vacations but also to savor recovery experiences while off work. In particular, experiencing new and challenging events during a vacation was the most significant predictor of vacationers’ subsequent well-being. Our results clarify what type of vacation is most effective for well-being. The results can help tourism practitioners manage their customers’ experiences better during their vacations, and these efforts will arguably contribute not only to the well-being of vacationers but also to future company growth.